Analisis Nilai-Nilai Dakwah pada Metode Komunikasi Antara Pelatih dengan Atlet Sepakbola Ma’had Al-Zaytun - Fauzi, Hilal Nur; Suryadari, Meity; Sulistyani, Anjar (Lembaga Pengembangan Kinerja Dosen, 2025)
This study examines the role of coach communication in fostering Ma’had Al-Zaytun football athletes as a medium of da’wah for instilling Islamic values. Departing from the importance of communication in character development, the purpose of this research is to analyze the da’wah values contained in the interaction between coach and athletes and to identify the da’wah communication methods employed. The study uses a descriptive qualitative approach with observation, interview, and documentation techniques conducted during training activities within the pesantren environment. The results indicate that the coach’s communication not only delivers technical instructions but also serves as a medium for the internalization of da’wah that al igns with Al-Zaytun’s vision of integral education; the value of aqidah is manifested through habitual worship, moral values are reflected in discipline, responsibility, politeness, solidarity, and sportsmanship, while sharia values are evident in obedience to worship and game rules. The communication methods used are natural and contextual, combining hikmah, mau’izhah hasanah, qaulan layyinan, and exemplary conduct; da’wah is internalized through direct interaction, coach exemplification, and practical on-field experiences. The findings affirm the effectiveness of sports training as a medium of da’wah that cultivates faithful, moral, and responsible athletes.